2005
DOI: 10.1038/nrmicro1236
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating prokaryotic species

Abstract: There is no widely accepted concept of species for prokaryotes, and assignment of isolates to species is based on measures of phenotypic or genome similarity. The current methods for defining prokaryotic species are inadequate and incapable of keeping pace with the levels of diversity that are being uncovered in nature. Prokaryotic taxonomy is being influenced by advances in microbial population genetics, ecology and genomics, and by the ease with which sequence data can be obtained. Here, we review the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
747
2
26

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 987 publications
(800 citation statements)
references
References 40 publications
8
747
2
26
Order By: Relevance
“…MLSA is widely used to understand the taxonomic relationships among bacterial populations (8,10,11), and it was the method we employed in an earlier study to suggest that M. ulcerans recently evolved from M. marinum (32). To improve genome coverage and increase resolution of the MLSA method for the present investigation, we added an eighth locus to create a 3,210-bp semantide (a large information-bearing molecule).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLSA is widely used to understand the taxonomic relationships among bacterial populations (8,10,11), and it was the method we employed in an earlier study to suggest that M. ulcerans recently evolved from M. marinum (32). To improve genome coverage and increase resolution of the MLSA method for the present investigation, we added an eighth locus to create a 3,210-bp semantide (a large information-bearing molecule).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequences of the alleles are listed in Table S3 in the supplemental material. The allelic profiles for some isolates differed at more than three of the eight loci, so phylogeny was inferred by using a distance method rather than a pairwise comparison of the allelic profiles (29); the latter approach is referred to as multilocus sequence typing (10). For each ST, the nucleotide sequences of the alleles were concatenated in frame to generate an artificial CDS.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence analysis of the 16S ribosomal RNA (rRNA) gene allows the construction of valid bacterial phylogenies (Schleifer 2009), but lacks resolving power at and below the species level, due to the extent of gene conservation (Willems 2006). Multilocus sequence analysis (MLSA) of conserved core genes was proposed as a robust and reliable alternative method for classifying bacteria to species level (Gevers et al 2005;Hanage et al 2006) and has been successfully used to delineate species within a number of genera including Ensifer, formerly Sinorhizobium (Martens et al 2008), and Bradyrhizobium (Rivas et al 2009). However, incongruent phylogenies have been reported among several genes commonly used in MLSA, along with evidence of lateral gene transfer or intergenic recombination, resulting in unclear taxonomic resolution Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, many authors have reported drawbacks with these methods (Ueda et al, 1999;Stackebrandt et al, 2002;Schouls et al, 2003;Stackebrandt, 2003;van Berkum et al, 2003;Eardly et al, 2005). The ad hoc Committee for the Re-evaluation of the Species Definition in Bacteriology (Stackebrandt et al, 2002;Gevers et al, 2005) suggested the sequence analysis of a set of protein-encoding genes as alternative phylogenetic markers, or multilocus sequence analysis (MLSA). Several recent studies have confirmed that sequences from housekeeping genes can be used for identification at the species level (Wertz et al, 2003;Zeigler, 2003), for evolutionary population genetics and in taxonomy (Stepkowski et al, 2003;Vinuesa et al, 2005a,b;Bailly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%